Pengaruh Profitabilitas, Likuiditas dan Solvabilitas Terhadap Pengungkapan CSR - Apsari, Della Putri Renata; Syaiful, Syaiful (Journal of Culture Accounting and Auditing, 2024)
This research aims to examine the influence of profitability, liquidity and solvency on corporate social responsibility disclosure. The sampling technique uses purposive sampling technique. The sample in this study consisted of 47 companies from a total population of 78 manufacturing companies in the consumer goods industry sector registered on the IDX in 2020-2022. Testing was carried out using multiple linear regression, F test and T test. The regression results show that Profitability has an effect on Corporate Social Responsibility. Liquidity has no effect on Corporate Social Responsibility. Solvency has no effect on Corporate Social Responsibility.